The association between serum uric acid level and changes of MRI findings in knee osteoarthritis: A retrospective study (A STROBE-compliant article) - Xiao, Lu (Medicine (Baltimore), 2019)
The objective of this study was to examine whether Magnetic resonance imaging (MRI) features of knee osteoarthritis (OA) had an association with the level of serum uric acid (SUA). The MRI of the OA patients from June 2015 to July 2017 were studied. The patients fulfilled the following inclusion criteria: 1) meet American College of Rheumatology (ACR) radiological and clinical criteria for OA of the knee, 2) age ≤ 65years old, 3) Body mass index (BMI) < 25 kg/m(2). Patients with OA were categorized into two groups based on the level of SUA. Patients with SUA level lower than 360 umol/L were recruited into the first group and the others were the second group. Odds ratios (OR) and 95% confidence intervals (CI) for SUA level and different MRI patterns were estimated with multivariable logistic regression.71 patients were included in this research. The mean age of the first group was 54.5 ± 8.4 and the second group was 55.6 ± 6.4. The Body Mass Index (BMI) of two groups was 22.7 ± 1.3 and 23.23 ± 1.9 separately. The mean SUA and creatinine (CR) level of the second group were 433.8 ± 70.6 umol/L and 80.1 ± 23.9 umol/L. There were statistically more focal erosions, osteophytes, bone marrow lesions and synovitis in the MRIs of the second group. A positive association between SUA level and synovitis as well as soft tissue swelling in MRIs was observed in patients with knee OA (OR = 1.017; 1.008, 95% CI: 1.007–1.028; 1.000–1.016). In conclusion, subjects with higher SUA level were more likely to have MRI abnormalities. OA patients need to lower their SUA level in order to keep the disease from progressing.